Quality of Life and Anxiety in Younger Patients after Biological versus Mechanical Aortic Valve Replacement - Kottmaier, Marc; Hettich, Ina; Deutsch, Marcus-André; Badiu, Catalin; Krane, Markus; Lange, Ruediger; Bleiziffer, Sabine (The Thoracic and Cardiovascular Surgeon, 2017)
Background Since biological valve recipients are likely to need a redo procedure in the future for valve deterioration, we hypothesized patients might be more fearful about the progression of their disease than patients after aortic valve replacement (AVR) with a mechanical valve. The aim of this study is to compare the quality of life (QOL) and anxiety in patients who have undergone biological versus mechanical AVR.Method A total of 56 patients after mechanical AVR (mean age: 64.4 ± 8.17 years) and 66 patients after biological AVR (mean age: 64.8 ± 11.05 years) received three questionnaires 5.66 (± 2.68) years after surgery, including: The short form-36 (SF-36) to assess QOL, the fear of progression questionnaire (FOP), and the cardiac anxiety questionnaire (CAQ) to assess general anxiety, anxiety related to cardiac symptoms, and anxiety about progression of heart disease and valve and anticoagulation-specific questions.Results No significant differences were found for all categories of the SF-36. The FOP showed significantly favorable values for the biological AVR group. The CAQ showed a tendency in the subscale “avoidance” (i.e., avoidance of pulse increase) and “attention” towards more favorable values for the biological AVR group.Conclusions In contrast to our hypothesis, patients after mechanical AVR show significantly higher anxiety values for the FOP, and a tendency toward higher values for “avoidance” (i.e., avoidance of pulse increase). Partnership concerns, especially in terms of sexuality can be explained by factors that are recognizable for the partner, such as valve sound. These data provide evidence that factors that are continuously present after mechanical AVR, such as valve sound or anticoagulation might affect wellbeing stronger than the certainty of reoperation in the future after biological AVR. We conclude that implantation of a biological prosthesis can be justified in younger patients with regards to QOL.
Keywords: aortic valve replacement; quality of life; cardiac anxiety; fear of progression